Longrun dynamics : a general economic and political theory - Snooks, G. D. (Graeme Donald) (Basingstoke : Macmillan, 1998)
Introduction. Dynamic approaches. Dynamic order. The driving force. The dynamic mechanism. The dynamic outcome. Politics and policy.
Keywords: Economics; Economics; Economic policy; Economic forecasting; Statics and dynamics (Social sciences)